2016
DOI: 10.1016/j.radonc.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between DNA damage responses of skin to a test dose of radiation and late adverse effects of earlier breast radiotherapy

Abstract: Residual DSB in skin following a 4Gy dose were not significantly associated with risk of late adverse effects of breast radiotherapy, although exploratory analyses suggested an association in severely affected individuals. By contrast, a significant association was detected based on the in vitro response of lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Furthermore, fibroblasts from the same patient also showed significant ex vivo radiosensitivity by γ-H2AX foci analysis [127]. More recently, ex vivo testing of lymphocytes by this technique has shown remarkable differences between groups of patients with high and low NTT grades, and/or enabled identification of patients at risk for higher grade toxicities in at least 13 publications [69,[128][129][130][131][132][133][134][135][136][137][138]. The main conclusion made in these studies was that the γ-H2AX assay may have a high potential for screening individual radiosensitivity among RT patients.…”
Section: γ-H2ax Focimentioning
confidence: 99%
“…Furthermore, fibroblasts from the same patient also showed significant ex vivo radiosensitivity by γ-H2AX foci analysis [127]. More recently, ex vivo testing of lymphocytes by this technique has shown remarkable differences between groups of patients with high and low NTT grades, and/or enabled identification of patients at risk for higher grade toxicities in at least 13 publications [69,[128][129][130][131][132][133][134][135][136][137][138]. The main conclusion made in these studies was that the γ-H2AX assay may have a high potential for screening individual radiosensitivity among RT patients.…”
Section: γ-H2ax Focimentioning
confidence: 99%
“…Various assays for cellular radiosensitivity have been evaluated as predictive tests for late reactions, mainly using patient lymphocytes or skin fibroblasts [7], [10], [11], [12]. The approach with the best evidence for predictive value is the radiation-induced lymphocyte apoptosis (RILA) assay.…”
Section: Introductionmentioning
confidence: 99%
“…Those latter patients displayed a delay in nucleoshuttling of the ATM protein in response to ionizing radiation of normal tissue. To date, no prospective study showed that one of those assays was able to predict severe late toxicities occurrence ( 26 , 27 ).…”
Section: Radio-induced Toxicity Biomarkers Eramentioning
confidence: 99%